Medical Ethics: Common or Uncommon Morality? - Rhodes, Rosamond (Cambridge quarterly of healthcare ethics, 2020)
This paper challenges the long-standing and widely accepted view that medical ethics is nothing more than common morality applied to clinical matters. It argues against Tom Beauchamp and James Childress’s four principles; Bernard Gert, K. Danner Clouser and Charles Culver’s ten rules; and Albert Jonsen, Mark Siegler, and William Winslade’s four topics approaches to medical ethics. First, a negative argument shows that common morality does not provide an account of medical ethics and then a positive argument demonstrates why the medical profession requires its own distinctive ethics. The paper also provides a way to distinguish roles and professions and an account of the distinctive duties of medical ethics. It concludes by emphasizing ways in which the uncommon morality approach to medical ethics is markedly different from the common morality approach.